Identification of parametric models with a priori knowledge of process properties - Janiszowski, Krzysztof B.; Wnuk, Paweł (Zielona Góra: Uniwersytet Zielonogórski)
An approach to estimation of a parametric discrete-time model of a process in the case of some a priori knowledge of the investigated process properties is presented. The knowledge of plant properties is introduced in the form of linear bounds, which can be determined for the coefficient vector of the parametric model studied. The approach yields special biased estimation of model coefficients that preserves demanded properties. A formula for estimation of the model coefficients is derived and combined with a recursive scheme determined for minimization of the sum of absolute model errors.
Keywords: absolute error measure; constrained parameters estimation; identification; parametric MISO models